2014
DOI: 10.1002/anie.201407744
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Asymmetric Transfer Hydrogenation of Olefins for the Synthesis of α‐ and β‐Amino Acids

Abstract: The field of asymmetric (transfer) hydrogenation of prochiral olefins has been dominated by noble metal catalysts based on rhodium, ruthenium, and iridium. Herein we report that a simple nickel catalyst is highly active in the transfer hydrogenation using formic acid. Chiral α- and β-amino acid derivatives were obtained in good to excellent enantioselectivity. The key toward success was the use of the strongly donating and sterically demanding bisphosphine Binapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(37 citation statements)
references
References 56 publications
0
36
0
1
Order By: Relevance
“…9 In 2014, Zhou et al reported the non-noble metal nickelcatalyzed asymmetric transfer hydrogenation for the preparation of b-amino acid derivatives in good to excellent enantioselectivities while only 30% ee and 10% yield were obtained for the substrate ethyl b-phenyl b-(phenylamino)acrylate. 10 In addition, organocatalytic asymmetric hydrosilylation of N-aryl b-enamino esters using HSiCl 3 as the reducing reagent has also emerged as an efficient alternative to transition metal-catalyzed hydrogenation for the synthesis of chiral b-amino acids derivatives. 11 Employing stoichiometric amounts of silane as reductant, copper hydride-catalyzed stereoselective conjugate reduction of b,b-disubstituted Michael acceptors represents a practical, efficient, and cost-effective method that generate enantioenriched carbonyl compounds possessing a tertiary stereocenter at the b-position.…”
Section: Introductionmentioning
confidence: 99%
“…9 In 2014, Zhou et al reported the non-noble metal nickelcatalyzed asymmetric transfer hydrogenation for the preparation of b-amino acid derivatives in good to excellent enantioselectivities while only 30% ee and 10% yield were obtained for the substrate ethyl b-phenyl b-(phenylamino)acrylate. 10 In addition, organocatalytic asymmetric hydrosilylation of N-aryl b-enamino esters using HSiCl 3 as the reducing reagent has also emerged as an efficient alternative to transition metal-catalyzed hydrogenation for the synthesis of chiral b-amino acids derivatives. 11 Employing stoichiometric amounts of silane as reductant, copper hydride-catalyzed stereoselective conjugate reduction of b,b-disubstituted Michael acceptors represents a practical, efficient, and cost-effective method that generate enantioenriched carbonyl compounds possessing a tertiary stereocenter at the b-position.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Mn-PNP-BH 3c was able to reduce only the C=Cd ouble bond in compound 15 a (Supporting Information, Scheme S2 and Figure S3). Homogeneous base metal-catalyzed reductions of alkenes and alkynes have been reported before with iron-, [10] cobalt-, [11] and nickel-based [12] catalysts and most of them use hydrogen sources other than EtOH. This is the first example of the use of am anganesebased pincer-catalyst for the TH of aC =Cbond using EtOH as hydrogen donor.…”
mentioning
confidence: 99%
“…[20] We recently disclosed a nickel/binapine catalyst for the asymmetric transfer hydrogenation of enamides. [21] Heterogeneous nickel catalysts modified with tartaric acid derivatives have been applied in the asymmetric hydrogenation of ketones (Orito reaction), although the success of this approach has been quite limited. [22] Herein, we describe the use of nickel catalysts for the asymmetric transfer hydrogenation of hydrazones and other ketimines.…”
mentioning
confidence: 99%